Does Internal Control Strengthen Fraud Detection Effectiveness? A Systematic Literature Review in The Role of Internal Control Measures in Combating Financial Fraud - A. Ikhwanul Ahmad; Muh. Farhan; Andi Kusumawati; Agus Bandang (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2025)
This study aims to examine the impact of internal control on the effectiveness of financial fraud detection in company financial statements, with a focus on high-volatility sectors. Utilizing a Systematic Literature Review (SLR) approach, the study identifies and analyzes literature related to internal control, technology in fraud detection, and the challenges auditors face in implementing effective internal controls. The results indicate that well-executed internal control systems can significantly enhance a company's ability to detect and prevent fraud. The study also emphasizes the importance of integrating advanced technologies, such as data analytics and artificial intelligence (AI), to improve the accuracy and efficiency of fraud detection. Moreover, key challenges in implementing effective internal control include reliance on auditor expertise and the need to continuously adjust policies to keep pace with rapidly changing market dynamics. These findings provide valuable insights for the future development of internal controls and offer a theoretical foundation for further research in this field.